2012
DOI: 10.1080/21528586.2012.694252
|View full text |Cite
|
Sign up to set email alerts
|

University–community engagement in South Africa: dilemmas in benchmarking

Abstract: The increasing value of community engagement activities in universities worldwide is yielding a rising emphasis on benchmarking university-community engagement. However, the emergence of effective benchmarks is still at an incipient stage. This article aims to provide some practical directions for developing a systematic approach to benchmarking university-community engagement within the South African milieu. The observation is made that comparative university experiences could provide useful insights into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Through a research initiative undertaken in a rural town in South Africa, Albertyn, Botha, Van der Merwe, Le Roux and Coetzee concluded that teaching and learning related to community development principles, planned activities, appropriate research methods, quality, ethical issues, sustainability and reciprocal benefits were the criteria to ensure an integrated approach to community engagement. Olowu's (2012) article provided greater insights into developing a systematic approval for benchmarking universitycommunity engagement in South Africa and is relevant to enabling institutionalisation of CE.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Through a research initiative undertaken in a rural town in South Africa, Albertyn, Botha, Van der Merwe, Le Roux and Coetzee concluded that teaching and learning related to community development principles, planned activities, appropriate research methods, quality, ethical issues, sustainability and reciprocal benefits were the criteria to ensure an integrated approach to community engagement. Olowu's (2012) article provided greater insights into developing a systematic approval for benchmarking universitycommunity engagement in South Africa and is relevant to enabling institutionalisation of CE.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This led to the development of multiple institutional assessment tools that reflect institutional commitment to community engagement through the university's mission, structures, leadership and through, faculty and community involvement (Furco, 1999;Holland, 2006). The development of effective benchmarking tools for university community engagement is still however, in its infancy in South Africa (Olowu, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there are very few tools available to assess community engagement efficiently. There is also no clearly defined benchmark of what effective community engagement would entail (Olowu, 2012). It is, however, possible to develop a conceptual framework that is unique to a specific institution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The conceptual framework should also be aligned with the wider development goals to be effective in its execution (Pienaar-Steyn, 2012). All being well, academics' performances can be measured and rewarded if there is an efficient system in place that provides a framework and benchmarking (Olowu, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%